Diversity for Better Quality of Community Life: Evaluations in Famagusta Neighbourhoods - Saeidi, Sanaz; Oktay, Derya (Elsevier Science Bv, 2012)
Physical qualities that create diversity in uses and users are the basis of well-functioning of the neighbourhood environment. However, since the Modernist period, there have been obvious shortcomings in planners' contribution to the concept of diversity within neighbourhood structure and spatial pattern in many cases. This study, therefore, first investigates the issue of diversity within neighbourhood environments and highlights its significance in achieving a successful neighbourhood; then, it will build up a model for analysis of diversity and will analyze four neighbourhoods of Famagusta based on a proposed model in order to make recommendations towards better quality of community life in neighbourhoods. (C) 2011 Published by Elsevier Ltd. Selection and peer-review under the responsibility of Centre for Environment-Behaviour Studies (cE-Bs), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia
Asia Pacific International Conference on Environment-Behaviour Studies (AicE-Bs) -- DEC 07-09, 2011 -- Eastern Mediterranean Univ (EMU), Urban Res & Dev Ctr (URDC), Famagusta, CYPRUS
Keywords: Neighbourhood; diversity; quality of community life; Famagusta neighbourhoods